USE OF ‘WOODEN DUMMY SOW’ FOR TRAINING OF BOAR FOR SEMEN COLLECTION AND THE SEMEN QUALITY OF TRAINED BOAR - CHUTIA, T; LALRINTLUANGA, K; AHMED, FA; LEGO, A (The Indian Journal of Animal Reproduction, 2022)
The present investigation indicated that boar can be trained through psychological intervention, without any hormonal treatment, using ‘wooden dummy sow’ for semen collection. Semen characteristics like sperm concentration (165.6 million/ml), sperm motility (76.2%) and live sperm (76.6%) of trained boar were within normal range with minimum morphological sperm abnormalities (9.9%). Also, HOST revealed the presence of quality sperms (70.5%) that was supported by successful conception rate (71.4%). Biochemical tests viz. ‘R’ test and MBR test as per protocol for bull semen were not fit for the quality assessment of boar semen. In brief, boar can be trained for semen collection using a dummy sow and the semen quality of trained boar was acceptable for AI.